Conservation of Repeats at the Mammalian KCNQ1OT1-CDKN1C Region Suggests a Role in Genomic Imprinting. (15th June 2017) - De Donato, Marcos; Hussain, Tanveer; Rodulfo, Hectorina; Peters, Sunday O; Imumorin, Ikhide G; Thomas, Bolaji N
KCNQ1OT1 is located in the region with the highest number of genes showing genomic imprinting, but the mechanisms controlling the genes under its influence have not been fully elucidated. Therefore, we conducted a comparative analysis of the KCNQ1/KCNQ1OT1-CDKN1C region to study its conservation across the best assembled eutherian mammalian genomes sequenced to date and analyzed potential elements that may be implicated in the control of genomic imprinting in this region. The genomic features in these regions from human, mouse, cattle, and dog show a higher number of genes and CpG islands (detected using cpgplot from EMBOSS), but lower number of repetitive elements (including short interspersed nuclear elements and long interspersed nuclear elements), compared with their whole chromosomes (detected by RepeatMasker). The KCNQ1OT1-CDKN1C region contains the highest number of conserved noncoding sequences (CNS) among mammals, where we found 16 regions containing about 38 different highly conserved repetitive elements (using mVista), such as LINE1 elements: L1M4, L1MB7, HAL1, L1M4a, L1Med, and an LTR element: MLT1H. From these elements, we found 74 CNS showing high sequence identity (>70%) between human, cattle, and mouse, from which we identified 13 motifs (using Multiple Em for Motif Elicitation/Motif Alignment and Search Tool) with a significant probability of occurrence, 3 of which were the most frequent and were used to find transcription factor–binding sites. We detected several transcription factors (using JASPAR suite) from the families SOX, FOX, and GATA. A phylogenetic analysis of these CNS from human, marmoset, mouse, rat, cattle, dog, horse, and elephant shows branches with high levels of support and very similar phylogenetic relationships among these groups, confirming previous reports. Our results suggest that functional DNA elements identified by comparative genomics in a region densely populated with imprinted mammalian genes may be related to the regulation of imprinted gene expression.